SWIFTER THAN EAGLES: A BRIEF HISTORY OF THE SOUTH AFRICAN AIR FORCE 1912-1982 - E.H. Ward (Scientia Militaria, 2012)
South African pioneers in the air Since time immemmorial, nation has waged war upon nation, both by land and by sea, yet it is only during this century that the air has evolved into a major theatre of war. Riding on the flood tide of a technology stimulated by two World Wars and the ever present need to remain prepared for the eventuality of an armed conflict, military aviation has, in a few short years, developed from relatively primitive beginnings into a highly effective and sophisticated weapon indispensable to a modern defence force. To a greater extent, he who controls the skies also controls the rest of the battlefield.